2014
DOI: 10.1080/00028487.2014.949011
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Juvenile Migration Tactics to Adult Recruitment in Stream‐Type Chinook Salmon Populations

Abstract: The existence of multiple migration tactics within a population has been observed for several fish species, and they may contribute differentially to adult recruitment. Relative contribution by juveniles using the same habitats on different schedules is variable; therefore, understanding and conserving this diversity should be important to fisheries managers. We investigated adult recruitment by two distinct juvenile migration tactics in several spawning populations of stream‐type Chinook Salmon Oncorhynchus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…For instance, Copeland et al. () found that a substantial proportion of juvenile spring/summer Chinook salmon in the Snake River rear downstream from their natal streams. Given that imprinting is believed to occur throughout their stream occupancy, this behavior could influence homing accuracy (Westley et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Copeland et al. () found that a substantial proportion of juvenile spring/summer Chinook salmon in the Snake River rear downstream from their natal streams. Given that imprinting is believed to occur throughout their stream occupancy, this behavior could influence homing accuracy (Westley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring dispersal from the natal population to the population in which animals reproduce may not completely represent dispersal processes for species with complex life history strategies such as salmon. For instance, Copeland et al (2014) found that a substantial proportion of juvenile spring/summer Chinook salmon in the Snake River rear downstream from their natal streams. Given that imprinting is believed to occur throughout their stream occupancy, this behavior could influence homing accuracy (Westley et al 2013).…”
Section: Impact Of Information Level On Metapopulation Characterizationmentioning
confidence: 99%
“…There could be several mechanisms responsible for this lone latent variable association, one of which could be alternative juvenile life history rearing strategies. Each year some proportion of juveniles leave their natal streams early and rear in downstream habitats in response to habitat and environmental conditions and perhaps other factors, and the Secesh River population is among those with a high proportion of downstream-rearing juveniles (Copeland et al 2014). These types of divergent latent variable association patterns may represent important components to MPG, ESU, and species diversity which may have implications for setting conservation priorities: specifically, prioritizing which populations to target for recovery efforts (A. Fullerton, S. Anzalone, D. Van Doornik, T. Copeland, P. Moran, and R. Zabel, In Review.).…”
Section: Discussionmentioning
confidence: 99%
“…; Copeland et al. ) plus sockeye and coho salmon ( O. kisutch ) with PIT detection histories in recent years. Ideally, empirical exposure data would be collected for these groups to assure that the relationship between observed and predicted DDs is consistent across species and life‐history types.…”
Section: Discussionmentioning
confidence: 99%
“…Similar population-specific analyses could be conducted for the dozens of wild and hatchery populations that are PIT-tagged in the Snake River basin each year (e.g., Muir et al 2001;Garcia et al 2004). There are also many stream-type Chinook salmon (e.g., Achord et al 2007;Copeland et al 2014) plus sockeye and coho salmon (O. kisutch) with PIT detection histories in recent years. Ideally, empirical exposure data would be collected for these groups to assure that the relationship between observed and predicted DDs is consistent across species and life-history types.…”
Section: Management Implicationsmentioning
confidence: 99%